2020
DOI: 10.1038/s41598-020-69931-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate as a potential prebiotic for the oral microbiome

Abstract: The salivary glands actively concentrate plasma nitrate, leading to high salivary nitrate concentrations (5-8 mM) after a nitrate-rich vegetable meal. Nitrate is an ecological factor that can induce rapid changes in structure and function of polymicrobial communities, but the effects on the oral microbiota have not been clarified. To test this, saliva of 12 healthy donors was collected to grow in vitro biofilms with and without 6.5 mM nitrate. Samples were taken at 5 h (most nitrate reduced) and 9 h (all nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
94
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 84 publications
16
94
2
3
Order By: Relevance
“…Another most common bacterial genus was Veillonella, especially in the tongue coatings of children (Fig. 5), which is consistent with the findings of Doel et al The present study supports the previous findings that Neisseria was one of the predominant NO 2 − -producing bacteria in the oral cavities of adults 9,11 . Furthermore, it was the first study to show that Neisseria accounted for a relatively high percentage of NO 2 − -producing bacteria in children (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Another most common bacterial genus was Veillonella, especially in the tongue coatings of children (Fig. 5), which is consistent with the findings of Doel et al The present study supports the previous findings that Neisseria was one of the predominant NO 2 − -producing bacteria in the oral cavities of adults 9,11 . Furthermore, it was the first study to show that Neisseria accounted for a relatively high percentage of NO 2 − -producing bacteria in children (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The modified agar overlay method used in the current study might be more useful for detecting NO 2 − -producing bacteria. www.nature.com/scientificreports/ Rothia is an NO 2 − -producing bacterium that is found in the oral cavity 9,12,13 . The present study showed that Rothia accounted for a high proportion of the NO 2 − -producing bacteria in children's tongue coatings (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, nitrate prevented acidification by oral bacteria (Li et al, 2007) and the nitrate reduction capacity (NRC) of the oral microbiota correlated negatively with caries abundance (Doel et al, 2004). Recently, Rosier et al (2020) have proposed that nitrate reduction stimulates eubiosis (i.e., an increase in health-associated species and functions) of the oral microbiota (Rosier et al, 2020). Specifically, nitrate reduction prevented acidification and the resulting overgrowth of cariogenic bacteria by increasing lactate consumption and ammonia production.…”
Section: Introductionmentioning
confidence: 99%